Дневник Кото-Сапиенса: [юмористическая повесть в рассказах] / Тамара Крюкова ; диктор В. Максимов - Крюкова Тамара Шамильевна (1С-Паблишинг, 2021)
Экземпляры: БС (20230907) / Инвентарный номер: ФЖД11915 / Сис.шифр: 84(2) / Авт.знак: К 85 / ГРНТИ: 17 / ББК: 84(2=411.2)6-4